A method for preparing a composite carbon support for platinum-based noble metal particles

CN116722160BActive Publication Date: 2026-10-27SHANGHAI TANGFENG ENERGY TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310678740.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-08
Publication Date
2026-10-27
Estimated Expiration
2043-06-08

AI Technical Summary

Technical Problem

[0004]但是,上述碳载体的制备采用了高成本的加工工艺,因此通过上述工艺过程来批量化制备催化剂材料仍然存在不少高问题

Benefits of technology

[0029]本发明开发的复合碳载体p-CB@rGO,兼具高石墨化度与导电性、等优势,可有效提升碳载体的稳定性与耐腐蚀性;本发明开发的催化剂材料中,复合碳载体的引入,可有效改善催化剂的稳定性和催化活性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116722160B_ABST
    Figure CN116722160B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a composite carbon carrier for loading platinum-based noble metal particles; a water-soluble polymer material and carbon black are dispersed in a solution to complete coating treatment of the carbon black by the polymer material; a graphene oxide dispersion liquid is added into the above solution to continue homogenization treatment; the above mixture is transferred into an inert atmosphere to perform heat treatment, carbon black nanoparticles can be uniformly dispersed and anchored on a graphene surface to obtain a composite carbon carrier p-CB@rGO; finally, a water solution containing platinum ions is added into a proper amount of the composite carbon carrier p-CB@rGO dispersion liquid according to a stoichiometric ratio to perform static treatment for several hours, after drying, the above mixture is transferred into a hydrogen atmosphere to perform heat treatment, and platinum-based noble metal particles will be in-situ grown and dispersed in the composite carbon carrier p-CB@rGO. The preparation method of the composite carbon carrier can effectively improve the stability and catalytic activity of a catalyst material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of fuel cell catalyst technology, specifically, it relates to a method for preparing a composite carbon support for supporting platinum-based noble metal particles. Background Technology

[0002] The structure and physicochemical properties of carbon supports have a crucial impact on the overall performance of fuel cell catalysts under actual operating conditions. Commonly used carbon supports for fuel cell catalysts include carbon black, Ketjen black, acetylene black, carbon nanotubes, graphene, and carbon fibers. Non-graphitized carbon supports are prone to corrosion under harsh conditions such as high potential operation in fuel cell systems; graphitized carbon supports typically suffer from low specific surface area and low dispersion. Graphene, as a two-dimensional lattice structure material with sp2 hybridized carbon atoms tightly packed together, possesses advantages such as high specific surface area, high graphitization degree, good water dispersibility, and good electrical conductivity, and is frequently considered as a carbon support for fuel cell catalysts.

[0003] Patent CN112687901A provides a three-dimensional graphene-supported platinum catalyst and its preparation method. Platinum is loaded onto three-dimensional graphene, allowing it to be uniformly dispersed on the surface perpendicular to the graphene sheet, resulting in a catalyst with uniform platinum dispersion and effectively improving platinum utilization. However, catalysts prepared using graphene alone as a carbon support suffer from poor processing consistency and graphene structure collapse during membrane electrode fabrication, leading to poor water / gas mass transfer. CN105833889A provides a platinum-supported catalyst based on a porous graphene / nanoceramic sandwich structure and its preparation method. The nanopores in the porous graphene facilitate the axial transport of water and reactant gases and the conduction of electrons and protons, while effectively providing sites for platinum loading and limiting the migration and aggregation of platinum nanoparticles on the support surface. Patent CN 109935846A provides a fuel cell electrocatalyst support and its preparation method. However, the carbon black selected in this patent is not graphitized or highly graphitized carbon material, and it does not address the difficulty of uniformly dispersing graphitized carbon black and graphene.

[0004] However, the preparation of the aforementioned carbon supports employs costly processing techniques, thus presenting significant challenges for the mass production of catalyst materials using these processes. Therefore, developing a composite carbon support that combines high graphitization with conductivity, high porosity, and strong hydrophilicity can effectively improve catalyst stability and activity, holding significant application and industrialization value for the development of novel catalysts. Summary of the Invention

[0005] The present invention aims to provide a method for preparing a composite carbon support for loading platinum-based noble metal particles. The method includes the following steps: First, a water-soluble polymer material and carbon black are dispersed in a solution at a certain ratio to complete the coating treatment of the carbon black by the polymer material; Second, a graphene oxide dispersion is added to the above solution for further homogenization; Third, the mixture is transferred to an inert atmosphere for heat treatment, allowing the carbon black nanoparticles to be uniformly dispersed and anchored on the graphene surface, resulting in the composite carbon support p-CB@rGO; Finally, a prepared aqueous solution containing platinum ions is added to an appropriate amount of the composite carbon support p-CB@rGO according to a stoichiometric ratio, and after standing for several hours and drying, the mixture is transferred to a hydrogen atmosphere for heat treatment. The above method for preparing the composite carbon support can effectively improve the stability and catalytic activity of the catalyst material.

[0006] Specifically, the objective of this invention is achieved through the following technical solutions:

[0007] In a first aspect, the present invention provides a method for preparing a composite carbon support for loading platinum-based noble metal particles, comprising the following steps:

[0008] S1. The water-soluble polymer material and carbon black are stirred and dispersed in the solution to complete the coating treatment of carbon black by the polymer material, and a mixture dispersion A is obtained.

[0009] S2. Add the dispersion containing graphene oxide to the mixture dispersion A, homogenize and freeze dry to obtain mixture B;

[0010] S3. The mixture B is transferred to an inert atmosphere and heat-treated at a temperature above 200°C for several hours. The carbon black nanoparticles are uniformly dispersed and anchored on the graphene surface to obtain the composite carbon carrier p-CB@rGO. The thickness of the carbon-coated carbon black is adjustable in the range of 2nm-100nm.

[0011] As one implementation scheme, in step S1, the water-soluble polymer material is one or a mixture of several of the following: polyethylene glycol, polyacrylic acid, acrylonitrile, polyvinyl alcohol, polyvinylpyrrolidone, carboxymethyl cellulose, cyclodextrin, polyoxyethylene ether, and modified versions of the above polymer materials. This invention effectively solves the problem of uneven dispersion of graphitized carbon black by using a special surfactant coating method. If water-soluble polymer materials not limited to those of this invention are used to coat carbon black, the excellent coating effect on graphitized carbon black cannot be achieved.

[0012] As one implementation, in step S1, the carbon black is at least one of graphitized carbon black, nano-graphite, graphitized carbon fiber, carbon nanotubes, etc.

[0013] As one implementation scheme, the mass ratio of water-soluble polymer materials, carbon black, and graphene oxide is 1-30:50-100:15-50; including 8-30:65-100:15-45.

[0014] As one implementation, the homogenization process takes 10 minutes to 12 hours; the freeze-drying temperature is -40℃ to 0℃ and the time is 6 hours to 72 hours; the heat treatment temperature is 200℃ to 600℃ and the time is 0.5 hours to 24 hours.

[0015] As one implementation method, a homogenization device is used to homogenize the dispersion once.

[0016] As one implementation, the homogenization equipment can be at least one of a high-pressure homogenizer, a micro-jet homogenizer, a nano-homogenizer, a high-shear dispersion emulsifier, an ultrasonic homogenizer, a probe-type vortex homogenizer, a tapping homogenizer, or a vacuum homogenizer / emulsifier.

[0017] As one implementation scheme, in step S3, the inert atmosphere is high-purity nitrogen, high-purity argon, high-purity helium, etc.

[0018] As one implementation, in step S3, the mass ratio m of carbon black in the composite carbon support p-CB@rGO to the total mass of carbon black and graphene is... p-CB / (m rGO +m p-CB The percentage of the positive charge is 20% to 98%. A range outside this range will result in poor overall battery performance.

[0019] Secondly, the present invention provides a method for preparing a catalyst based on platinum-based noble metal particles supported on a composite carbon support, the method comprising the following steps:

[0020] A1. According to the stoichiometric ratio, the prepared aqueous solution containing platinum ions is added to the composite carbon support p-CB@rGO prepared by the above method and allowed to stand for several hours (e.g., 1-6 hours), and then freeze-dried to obtain mixture C.

[0021] A2. The mixture C is transferred to a hydrogen atmosphere and heat-treated at a temperature above 200°C (e.g., 300-850°C) for several hours (e.g., 2-4 hours). The platinum-based noble metal particles will grow in situ and disperse in the composite carbon support p-CB@rGO to obtain catalyst D.

[0022] As one implementation, in step A1, the aqueous solution containing platinum ions is an aqueous solution of at least one of chloroplatinic acid, sodium chloroplatinate, potassium chloroplatinate, other platinum salts, platinum-based metal complexes, and platinum-based metal complexes.

[0023] As one implementation, in step A1, the aqueous solution containing platinum ions is a mixed solution based on an atomic ratio of transition metal to platinum of 1:(1-10), wherein the transition metal is selected from a solution of at least one metal salt selected from cobalt, nickel, manganese, iron, copper, palladium, iridium and ruthenium.

[0024] As one implementation, in step A2, the hydrogen atmosphere is high-purity hydrogen, a 5%-50% hydrogen-argon mixture, or a hydrogen-nitrogen mixture.

[0025] As one implementation, in step A2, the reducing agent is a mixture of at least one or more of sodium borohydride, hydrazine hydrate, ascorbic acid, ethylene glycol, glycerol, and other soluble reducing agents.

[0026] As one implementation scheme, in step A1, the stoichiometric ratio corresponds to a platinum-carbon mass ratio of 80–50:0–50. This includes 80–50:10–50, such as 60:40, 50:40, etc.

[0027] As one embodiment, in step A2, the ratio of the mass of precious metals in the catalyst to the total mass of the catalyst is 0% to 90%. Preferably, the ratio of the mass of precious metals in the catalyst to the total mass of the catalyst can be 5% to 75%.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] The composite carbon support p-CB@rGO developed in this invention has the advantages of high graphitization degree and conductivity, which can effectively improve the stability and corrosion resistance of the carbon support; in the catalyst material developed in this invention, the introduction of the composite carbon support can effectively improve the stability and catalytic activity of the catalyst. Attached Figure Description

[0030] Other features, objects, and advantages of the present invention will become more apparent from the following detailed description of non-limiting embodiments with reference to the accompanying drawings:

[0031] Figure 1 A schematic diagram of the composite carbon support p-CB@rGO designed for this invention;

[0032] Figure 2 This is a schematic diagram of the composite carbon support CB / rGO in Comparative Example 1;

[0033] Figure 3 This is a schematic diagram of the platinum-based catalyst based on the composite carbon support p-CB@rGO designed in this invention;

[0034] Figure 4 A schematic diagram of a platinum-based catalyst based on the composite carbon support CB / rGO designed for Comparative Example 1. Detailed Implementation

[0035] The present invention will now be described in detail with reference to specific embodiments. These embodiments will help those skilled in the art to further understand the present invention, but do not limit the invention in any way. It should be noted that those skilled in the art can make several changes and improvements without departing from the concept of the present invention. These all fall within the protection scope of the present invention.

[0036] Example 1

[0037] The preparation method of a composite carbon support for loading platinum-based noble metal particles in this embodiment is as follows:

[0038] (1) 8g of water-soluble polyethylene glycol and 80g of graphitized material with a specific surface area of ​​~600m² were mixed. 2 / g of carbon black was stirred and dispersed in 500ml of water / ethanol mixed solution to complete the coating treatment of the above carbon black with polymer material, and the mixture dispersion A was obtained.

[0039] (2) Add 500g of the dispersion containing 25g of graphene oxide to the above mixture dispersion A, and use a vacuum homogenizer to homogenize the dispersion once for 30 minutes. Then freeze dry at -30℃ for 24 hours to obtain mixture B.

[0040] (3) The above mixture B was transferred to an argon atmosphere and heat-treated at 500℃ for 2 hours. The carbon black nanoparticles were uniformly dispersed and anchored on the graphene surface to obtain the composite carbon support p-CB@rGO. The thickness of the carbon-coated carbon black was approximately 10 nm. The mass ratio of carbon black to the total mass of carbon black and graphene in the composite carbon support p-CB@rGO was m. p-CB / (m rGO +m p-CB ) is 80%;

[0041] (4) According to the mass ratio of platinum to carbon of 50:50, the prepared chloroplatinic acid aqueous solution was added to 50g of composite carbon carrier p-CB@rGO and allowed to stand for 6 hours. Then, it was freeze-dried at -30℃ for 24 hours to obtain mixture C.

[0042] (5) The above mixture C is transferred into a hydrogen atmosphere and heat-treated at 300°C for 4 hours. Platinum metal particles will grow in situ and disperse in the composite carbon support p-CB@rGO to obtain Pt / C catalyst D.

[0043] The schematic diagram of the composite carbon support p-CB@rGO designed in Example 1 is shown below. Figure 1 As shown, carbon black nanoparticles can be uniformly dispersed and anchored on the graphene surface. The thickness of the carbon-coated carbon black is adjustable within the range of 10 nm.

[0044] The schematic diagram of the Pt / C catalyst designed in Example 1 and the distribution of platinum particles are shown below. Figure 3 Platinum metal particles were dispersed in the composite carbon support p-CB@rGO, with an average particle size of 3 nm. RDE analysis showed that the catalyst had a specific activity of 0.12 A / mg at 0.9 V. Pt MEA battery testing shows that at 2000mA / cm 2 Tested at current densities, with an initial voltage above 0.65V, ECSA Loss% (0.6V-0.9V, 30k square wave) was less than 36%, and the catalytic activity decay (between 1.0V-1.5V, 5k triangular wave) was less than 35%.

[0045] Example 2

[0046] The preparation method of a composite carbon support for loading platinum-based noble metal particles in this embodiment is as follows:

[0047] (1) Mix 30g of polyoxyethylene ether surfactant with 70g of nano-graphite (average particle size of 50nm, specific surface area of ​​700m²). 2 / g) was stirred and dispersed in 500ml of water / ethanol mixed solution to complete the coating treatment of polyoxyethylene ether on nanographite, and the mixture dispersion A was obtained;

[0048] (2) Add 500g of an aqueous dispersion containing 20g of graphene oxide to the above mixture dispersion A, and use a microfluidic homogenizer to homogenize the dispersion once for 90 minutes. Then freeze-dry at -30℃ for 24 hours to obtain mixture B.

[0049] (3) The above mixture B was transferred to an argon atmosphere and heat-treated at 400℃ for 3 hours. The nano-graphite nanoparticles were uniformly dispersed and anchored on the graphene surface, resulting in the composite carbon support p-CB@rGO. The thickness of the carbon-coated nano-graphite was approximately 5 nm. The mass ratio of nano-graphite to the total mass of nano-graphite and graphene in the composite carbon support p-CB@rGO was m. p-CB / (m rGO +m p-CB ) is 70%;

[0050] (4) According to the mass ratio of platinum to carbon of 60:40, the prepared chloroplatinic acid aqueous solution was added to 40g of composite carbon carrier p-CB@rGO and allowed to stand for 6 hours. Then, it was freeze-dried at -30℃ for 48 hours to obtain mixture C.

[0051] (5) The above mixture C is transferred into a hydrogen atmosphere and heat-treated at 400°C for 2 hours. Platinum metal particles will grow in situ and disperse in the composite carbon support p-CB@rGO to obtain Pt / C catalyst D.

[0052] The schematic diagram of the composite carbon support p-CB@rGO designed in Example 2 is shown below. Figure 1 As shown, the nano-graphite nanoparticles can be uniformly dispersed and anchored on the graphene surface. The thickness of the carbon-coated nano-graphite is adjustable within the range of 5 nm.

[0053] The schematic diagram of the Pt / C catalyst designed in Example 2 and the distribution of platinum particles are shown below. Figure 3 Platinum metal particles are uniformly dispersed in the composite carbon support p-CB@rGO, with an average particle size of 3.5 nm. RDE analysis shows that the catalyst has a specific activity of 0.13 A / mg at 0.9 V. Pt MEA battery testing shows that at 2000mA / cm 2 Tested at current densities, with an initial voltage above 0.65V, ECSA Loss% (0.6V-0.9V, 30k square wave) was less than 35%, and the catalytic activity decay (between 1.0V-1.5V, 5k triangular wave) was less than 32%.

[0054] Example 3

[0055] The preparation method of the composite carbon support for the supported platinum-cobalt alloy catalyst in this embodiment is as follows:

[0056] (1) The specific surface area of ​​15g polyethylene glycol, 15g polyvinyl alcohol and 65g graphitized material is ~900m². 2 / g of carbon black was stirred and dispersed in 500ml of water / ethanol mixed solution to complete the coating treatment of carbon black with polyoxyethylene ether, and the mixture dispersion A was obtained.

[0057] (2) Add 500g of an aqueous dispersion containing 45g of graphene oxide to the above mixture dispersion A, and use an ultrasonic homogenizer to homogenize the dispersion once for 2 hours. Then freeze-dry at -30℃ for 24 hours to obtain mixture B.

[0058] (3) The above mixture B was transferred to an argon atmosphere and heat-treated at 450℃ for 1 hour. The carbon black nanoparticles were uniformly dispersed and anchored on the graphene surface to obtain the composite carbon carrier p-CB@rGO. The thickness of the carbon-coated carbon black was approximately 8 nm. The mass ratio of carbon black to the total mass of carbon black and graphene in the composite carbon carrier p-CB@rGO was m. p-CB / (m rGO +m p-CB The percentage is 65%.

[0059] (4) According to the mass ratio of platinum, cobalt and carbon of 50:10:40, the prepared chloroplatinic acid water and cobalt chloride solution were added to 40g of composite carbon carrier p-CB@rGO and allowed to stand for 6 hours. Then, the mixture was freeze-dried at -30℃ for 36 hours to obtain mixture C.

[0060] (5) The above mixture C is transferred into a hydrogen-argon mixed atmosphere and heat-treated at 850°C for 2 hours. The platinum-cobalt alloy particles will grow in situ and disperse in the composite carbon support p-CB@rGO to obtain PtCo / C catalyst D.

[0061] In the PtCo / C alloy catalyst designed in Example 3, platinum-cobalt alloy particles are uniformly dispersed in the composite carbon support p-CB@rGO, with an average particle size of 5 nm. RDE analysis showed that the catalyst exhibits a specific activity of 0.35 A / mg at 0.9 V. Pt MEA battery testing shows that at 2000mA / cm 2 Tested at current densities, with an initial voltage above 0.63V, ECSA Loss% (0.6V-0.9V, 30k square wave) was less than 43%, and the catalytic activity decay (between 1.0V-1.5V, 5k triangular wave) was less than 40%.

[0062] Example 4

[0063] The preparation method of the composite carbon support for the supported platinum-cobalt-manganese alloy catalyst in this embodiment is as follows:

[0064] (1) The specific surface area of ​​10g polyethylene glycol, 10g cyclodextrin and 90g graphitized material is ~500m². 2 / g of carbon black was stirred and dispersed in 500ml of water / ethanol mixed solution to complete the coating treatment of carbon black with polyoxyethylene ether, and the mixture dispersion A was obtained.

[0065] (2) Add 500g of an aqueous dispersion containing 15g of graphene oxide to the above mixture dispersion A, and use a tapping homogenizer to homogenize the dispersion once for 45 minutes. Then freeze-dry at -30℃ for 24 hours to obtain mixture B.

[0066] (3) The above mixture B was transferred to an argon atmosphere and heat-treated at 600℃ for 0.5 hours. The carbon black nanoparticles were uniformly dispersed and anchored on the graphene surface to obtain the composite carbon carrier p-CB@rGO. The thickness of the carbon-coated carbon black was approximately 6 nm. The mass ratio of carbon black to the total mass of carbon black and graphene in the composite carbon carrier p-CB@rGO was m. p-CB / (m rGO +m p-CB The percentage is 90%.

[0067] (4) According to the mass ratio of platinum, cobalt, manganese and carbon of 50:5:5:40, the prepared chloroplatinic acid water, cobalt chloride and manganese chloride solution were added to 40g of composite carbon carrier p-CB@rGO and allowed to stand for 6 hours. Then, the mixture was freeze-dried at -30℃ for 24 hours to obtain mixture C.

[0068] (5) The above mixture C is transferred into a hydrogen-argon mixed atmosphere and heat-treated at 850°C for 2 hours. The platinum-cobalt alloy particles will grow in situ and disperse in the composite carbon support p-CB@rGO to obtain PtCo / C catalyst D.

[0069] In the PtCoMn / C alloy catalyst designed in Example 4, platinum-cobalt alloy particles are uniformly dispersed in the composite carbon support p-CB@rGO, with an average particle size of 5 nm. RDE analysis showed that the catalyst exhibits a specific activity of 0.33 A / mg at 0.9 V. Pt MEA battery testing shows that at 2000mA / cm 2 Tested at current density, with an initial voltage above 0.62V, ECSALoss% (0.6V-0.9V, 30k square wave) was less than 40%, and the catalytic activity decay (between 1.0V-1.5V, 5k triangular wave) was less than 40%.

[0070] Comparative Example 1

[0071] The preparation method of a composite carbon support for loading platinum-based noble metal particles in this comparative example is as follows:

[0072] (1) 80g of ungraphitized material with a specific surface area of ​​~600m² 2 / g of carbon black was stirred and dispersed in 500ml of water / ethanol mixed solution to obtain mixture dispersion A;

[0073] (2) Add 500g of the dispersion containing 25g of graphene oxide to the above mixture dispersion A, and use a vacuum homogenizer to homogenize the dispersion once for 30 minutes. Then freeze dry at -30℃ for 24 hours to obtain mixture B.

[0074] (3) The above mixture B was transferred to an argon atmosphere and heat-treated at 350°C for 2 hours to obtain the composite carbon support CB / rGO. The thickness of the carbon black coating was approximately 10 nm; the mass ratio of carbon black to the total mass of carbon black and graphene in the composite carbon support CB / rGO was m. p-CB / (m rGO +m p-CB ) is 80%;

[0075] (4) According to the mass ratio of platinum to carbon of 50:50, the prepared chloroplatinic acid aqueous solution was added to 50g of composite carbon carrier CB / rGO and allowed to stand for 6 hours. Then, it was freeze-dried at -30℃ for 48 hours to obtain mixture C.

[0076] (5) The above mixture C is transferred into a hydrogen atmosphere and heat-treated at 200°C for 4 hours. Platinum metal particles will grow in situ and disperse in the composite carbon support CB / rGO to obtain Pt / C catalyst D.

[0077] The schematic diagram of the composite carbon support CB / rGO designed in Comparative Example 1 is shown below. Figure 2 As shown, carbon black nanoparticles are mostly dispersed in aggregated clusters on graphene. A schematic diagram of the structure and platinum particle distribution of the Pt / C catalyst designed in Comparative Example 1 is shown below. Figure 4 As shown, in the prepared Pt / C catalyst, platinum metal particles are mostly agglomerated and dispersed in medium CB / rGO, with an average particle size greater than 7 nm. RDE analysis showed that the catalyst has a specific activity of 0.06 A / mg at 0.9 V. Pt MEA battery testing shows that at 2000mA / cm 2 Tested at current densities, with an initial voltage above 0.60V, ECSA Loss% (0.6V-0.9V, 30k square wave) was less than 60%, and the catalytic activity decay (between 1.0V-1.5V, 5k triangular wave) was less than 50%.

[0078] Comparative Example 2

[0079] The preparation method of a graphene carrier for loading platinum-based noble metal particles in this comparative example is as follows:

[0080] (1) 1000g of an aqueous dispersion containing 105g of graphene oxide was homogenized once using a vacuum homogenizing emulsifier for 30 minutes, and then freeze-dried at -30℃ for 24 hours to obtain mixture B.

[0081] (2) The above mixture B was transferred into an argon atmosphere and heat-treated at 350°C for 2 hours to obtain graphene carbon support rGO;

[0082] (3) According to the mass ratio of platinum to carbon of 50:50, the prepared chloroplatinic acid aqueous solution was added to 50g of graphene carbon support rGO and allowed to stand for 6 hours. Then, it was freeze-dried at -30℃ for 24 hours to obtain mixture C.

[0083] (4) The above mixture C is transferred into a hydrogen atmosphere and heat-treated at 400°C for 4 hours. Platinum metal particles will grow in situ and disperse in the graphene carbon support rGO to obtain Pt / C catalyst D.

[0084] In the Pt / C catalyst prepared in Comparative Example 2, platinum metal particles were mostly agglomerated and dispersed on medium rGO, with an average particle size greater than 10 nm. RDE analysis showed that this catalyst had a specific activity of 0.05 A / mg at 0.9 V. Pt MEA battery testing shows that at 2000mA / cm 2 Tested at current densities, with an initial voltage above 0.55V, ECSA Loss% (0.6V-0.9V, 30k square wave) was less than 65%, and the catalytic activity decay (between 1.0V-1.5V, 5k triangular wave) was less than 55%.

[0085] Specific embodiments of the present invention have been described above. It should be understood that the present invention is not limited to the specific embodiments described above, and those skilled in the art can make various changes or modifications within the scope of the claims, which do not affect the essence of the present invention. Unless otherwise specified, the embodiments and features described in this application can be arbitrarily combined with each other.

Claims

1. A method for preparing a composite carbon support for loading platinum-based noble metal particles, characterized in that, The method includes the following steps: S1. A water-soluble polymer material and carbon black are stirred and dispersed in a solution to complete the coating treatment of carbon black by the polymer material, resulting in a mixture dispersion A; the water-soluble polymer material is one or a mixture of several of the following: polyethylene glycol, polyacrylic acid, acrylonitrile, polyvinyl alcohol, polyvinylpyrrolidone, carboxymethyl cellulose, cyclodextrin, polyoxyethylene ether, and modified versions of the above polymer materials; the carbon black is at least one of graphitized carbon black, nano-graphite, graphitized carbon fiber, and carbon nanotubes. S2. Add the dispersion containing graphene oxide to the mixture dispersion A, homogenize and freeze dry to obtain mixture B; the mass ratio of water-soluble polymer material, carbon black and graphene oxide is 1~30:50~100:15~50. S3. The mixture B is transferred to an inert atmosphere and heat-treated at a temperature above 200°C for several hours. The carbon black nanoparticles are uniformly dispersed and anchored on the graphene surface to obtain the composite carbon carrier p-CB@rGO. The thickness of the carbon-coated carbon black is adjustable in the range of 2nm-100nm.

2. The method for preparing a composite carbon support for loaded platinum-based noble metal particles according to claim 1, characterized in that, The homogenization process takes 10 minutes to 12 hours; the freeze-drying process takes 6 hours to 72 hours at a temperature of -40°C to 0°C; and the heat treatment process takes 0.5 hours to 24 hours at a temperature of 200°C to 600°C.

3. The method for preparing a composite carbon support for loaded platinum-based noble metal particles according to claim 1, characterized in that, In step S3, the mass ratio of carbon black in the composite carbon support p-CB@rGO to the total mass of carbon black and graphene is... m p-CB / ( m rGO +m p-CB ) The percentage is 20% to 98%.

4. A method for preparing a catalyst based on platinum-based noble metal particles supported on a composite carbon support, characterized in that, The method includes the following steps: A1. The prepared aqueous solution containing platinum ions was added to the composite carbon support p-CB@rGO prepared by the method described in claim 1 according to the stoichiometric ratio, and after standing treatment, it was freeze-dried to obtain mixture C; A2. The mixture C is transferred to a hydrogen atmosphere or a reducing agent for heat treatment at a temperature above 200°C. The platinum-based noble metal particles will grow in situ and disperse in the composite carbon support p-CB@rGO to obtain catalyst D.

5. The method for preparing a catalyst based on platinum-based noble metal particles supported on a composite carbon support according to claim 4, characterized in that, In step A1, the aqueous solution containing platinum ions is an aqueous solution of at least one of chloroplatinic acid, sodium chloroplatinate, potassium chloroplatinate, and platinum-based metal complexes, or a mixed solution based on an atomic ratio of transition metal to platinum of 1:(1-10), wherein the transition metal is selected from a solution of at least one metal salt selected from cobalt, nickel, manganese, iron, copper, palladium, iridium, and ruthenium.

6. The method for preparing a catalyst based on platinum-based noble metal particles supported on a composite carbon support according to claim 4, characterized in that, In step A2, the hydrogen atmosphere is high-purity hydrogen, a 5%-50% hydrogen-argon mixture, or a hydrogen-nitrogen mixture; the reducing agent is at least one or a mixture of several of sodium borohydride, hydrazine hydrate, ascorbic acid, ethylene glycol, and glycerol.

7. The method for preparing a catalyst based on platinum-based noble metal particles supported on a composite carbon support according to claim 4, characterized in that, In step A1, the stoichiometric ratio corresponds to a platinum-carbon mass ratio of 80~50:0~50; in step A2, the ratio of the mass of the noble metal in the catalyst to the total mass of the catalyst is 0~90%.

Citation Information

Patent Citations

  • Platinum supported catalyst based on porous graphene / nano ceramic sandwiched structure and preparation method thereof

    CN105833889A

  • Fuel cell electrocatalyst carrier and preparation method thereof

    CN109935846A

  • Three-dimensional graphene platinum-loaded catalyst as well as preparation method and application thereof

    CN112687901A

  • Platinum-cobalt alloy catalyst, preparation method and application thereof

    CN115133050A